Distributed Energy-Efficient Topology Control Algorithm in Home M2M Networks - Chao-Yang Lee; Chu-Sing Yang (International Journal of Distributed Sensor Networks)
Because machine-to-machine (M2M) technology enables machines to communicate with each other without human intervention, it could play a big role in sensor network systems. Through wireless sensor network (WSN) gateways, various information can be collected by sensors for M2M systems. For home M2M networks, this study proposes a distributed energy-efficient topology control algorithm for both topology construction and topology maintenance. Topology control is an effective method of enhancing energy efficiency and prolonging network lifetime. During the topology construction phase, each node builds a new topology based on the best parent node. Nodes can extend the network lifetime by adjusting transmission power to control the topology. In the topology maintenance phase, each node monitors the energy status of neighbors and triggers topology construction as needed. By balancing energy consumption, topology maintenance also avoids the hot spot problem. Simulation results confirm the superior performance of the proposed algorithm for distributed energy-efficient topology control (DETC) in terms of energy efficiency and network lifetime in home M2M networks.